Colombia - Rural Finance : Access Issues, Challenges and Opportunities - World Bank (Washington, DC, 2013)
The history of rural - mostly agricultural - finance in Colombia, is characterized by a system which channels benefits to limited numbers of beneficiaries, at the expense of the public sector, and the economy as a whole. A legacy of powerful agricultural lobbies (coffee, livestock) has translated into sector-biased legislation, that established the "Sistema Nacional de Credito Agropecuario" (National Agricultural Credit System), and related institutions. Nonetheless, current agricultural policies send mixed signals in terms of the degree of protection vs. subjection to market forces producers can expect, thus preventing the development of a profitable, and competitive agriculture. Against this background, the advent of a new administration faced a rather dangerous policy juncture, as the pressure to tackle poverty in rural areas, coincides with severe fiscal, and public debt constraints. The Government however, has now the opportunity to build substantive reforms in the financial sector, enacted under previous regimes. The study found that access to financial services in rural Colombia is limited and segmented, whose causes are traced to inadequate services, lack of innovation in financial intermediation in rural areas, and, to an outdated model of public intervention in agricultural credit. Recommendations center on a re-direction of public interventions, aimed at substantially expanding institutional outreach, and financial services and quality in rural areas. Recommended reforms would exploit the existing private (including cooperative) and public retail institutional base, and, the skills and capabilities in the two main institutions, one playing as second-tier institution a strong development agency role, and the other as a lead innovator in rural microfinance. Also suggested is a substantial revision of the usury law, and reforms of the legal and judicial framework, for the use of moveable property as collateral.